The use of dengue nonstructural protein 1 antigen for the early diagnosis during the febrile stage in patients with dengue infection - Ampaiwan Chuansumrit (2018)
BACKGROUND: To evaluate the use of dengue nonstructural protein 1 (NS1) antigen for the early diagnosis during the febrile stage in patients with dengue infection. METHODS: A total of 445 sera obtained from 165 patients [dengue fever (DF): 42, dengue hemorrhagic fever (DHF) grade I: 50, II: 63, III and IV: 10] and 8 other febrile illnesses 5-15 years of age, were assayed for the NS1 antigen, dengue-specific Ig M and Ig G antibodies. RESULTS: The positive rates of NS1 antigen among patients with either DF or DHF was 100% (7 of 7) on day 2, 92.3% (12 of 13) on day 3, 76.9% (40 of 52) on day 4, 56.5% (61 of 108) on day 5 of fever; and declined to 43.1% (59 of 137) on day 6 with defervescence and 29.8% (25 of 84) on day 7 (1 day after defervescence). The positive rates of patients with DF were higher than those with DHF but no statistically significant difference was found. However, patients with primary DHF infection had significantly higher positive rates than those with secondary DHF infection. The positive rates of Ig M antibodies were in reverse proportion to those of NS1 antigen. The additional Ig M antibody determination increased the positive rates to 90.4% (47 of 52) on day 4, 83.3% (90 of 108) on day 5 of fever; 95.6% (131 of 137) on day 6 with defervescence, and 88.1% (74 of 84) on day 7. CONCLUSIONS: Dengue NS1 antigen testing is suggested as a helpful tool for the early diagnosis of dengue infection after the onset of fever. The additional Ig M antibody determination increased the diagnostic rates. © 2008 Lippincott Williams & Wilkins, Inc.